Suomen maatalous 1997 - Kallio, Panu; Knuuttila, Marja; Linjakumpu, Hannu; Marttila, Juha; Vehkasalo, Ville (Maatalouden taloudellinen tutkimuslaitos, 1998)
Vuosikatsauksessa luodaan yleiskuva Suomen maataloustuotantoon, hintoihin, kulutukseen, tuloihin sekä nykyiseen maatalouspolitiikkaan hinta- ja tukijärjestelmineen. Myös rakenne-, ympäristö- ja sosiaalipolitiikkaa käydään julkaisussa läpi. EU:n komission Agenda 2000 -esityksen peruslinjat tuodaan esiin niin ikään.

The crop of 1997 was in accordance with the long-term trend, despite the cold early part of the summer, which delayed the sowing. After June the weather was hot and the growth was more rapid than usually. The total amount of cereals harvested was 3.8 bill. kg, and this exceeded that of 1996 by 2.7%. The total yield measured as fodder units was 3% higher than in 1996. There was some increase in both the area and the average yields. The area under set-aside decreased by almost 10%. Milk production started to grow in 1997. The quantities produced on farms that continued their production grew considerable, because the number of milk suppliers fell by 1,900. The average yield/cow grew by almost 200 l. In terms of the structural development the high price of milk quotas has been considered problematic, and partly administered quota trade was introduced in 1997. Pigmeat production grew by 5%. The market prices started to rise in June. There was some increase in beef production, too, but the price of beef decreased from the previous year. Poultry meat consumption continued to grow, and the production also grew by almost 10%. The decrease in egg production was not large enough to solve the serious market problems due to oversupply. Both agricultural imports and exports grew in 1997. Dairy products, meat, and cereals were imported more than in the previous year. Cereal imports decreased clearly, but the imports of more highly processed foods grew. There were no major changes in the consumer prices or in the consumption. Cheese consumption started to decrease slightly, which is contrary to the trend in the past few years. The consumption of eggs and pigmeat fell, too. The agricultural income in 1997 was about FIM 6.6 bill., which is about 1% lower than in 1996. The production volume grew, but the agricultural aid declined. The prices of production inputs rose by about 2%, and the producer prices fell a little over 1%. More investments were made in agriculture than for a long time. Investments were encouraged by public aid. In 1997 loans and subsidies were granted for altogether 15,000 projects, and the cost estimates of these totaled FIM 4.2 bill. The aid amounted to over FIM 900 mill. Investment aid was mainly directed to increasing the farm size and environmental investments. The small size of Finnish farms affects their competitiveness on the single market, and environmental aid requires considerable investments in livestock production. The year 1997 did not bring along any major changes in agricultural production or prices of the products. The future of Finnish agriculture involves a great deal of uncertainty. National aid consists of many different measures, and the decision on the continuation of many of these must be decided on in the negotiations before the end of 1999. The proposals of the Commission for a reform of the common agricultural policy are difficult for Finland, where agriculture operates in extremely adverse natural conditions.
Keywords: Ma; Suomi; maatalous; tulot; maataloustuotanto; maatalouspolitiikka; ympäristöpolitiikka; Finland; agriculture; production; price; income; policy